Análise da susceptibilidade geoambiental na bacia hidrográfica do Ribeirão Lajeado – Tocantins - Ribeiro, Lucas da Silva (2022)
The Geoenvironmental Zoning, through the integration of natural elements with the use and occupation of the land, becomes a fundamental methodological proposal for the strategic planning of a certain area, due to its application in different approaches and levels of exploration. Thus, the present work has as general objective to carry out an analysis of Geoenvironmental Susceptibility in the Ribeirão Lajeado hydrographic basin. Theoretical foundation was sought in studies on Hydrographic Basins, Geomorphological Characterization, Land Use and Occupation Studies in Environmental Analysis, Geoenvironmental Studies, Nature Conservation Units, Applied Geotechnologies in Environmental Studies and AHP Methodology of Multicriteria Analysis. The Methodological Procedures were carried out in stages, namely, Bibliographic Surveys, Acquisition and Manipulation of Cartographic Data. The main data used were vector (Roads, Municipalities, Municipal Headquarters, Conservation Units, Lithology and Soils) and raster (SRTM and satellite image). Through the SRTM/Topodata images it was possible to obtain the hypsometry, slope, topographic profiles, relief elements, drainage network and automatic delimitation of the hydrographic basin. The Landsat 8 satellite image, OLI sensor from July 2021, made it possible to carry out the supervised classification that generated the Land Use and Occupation map. Using the AHP technique, the normalized weights were acquired for each class of factors Land Use and Occupation, Roads, Slope, Drainage Network, Soils and Lithologies. Then the crossing was carried out in the raster calculator of the QGIS software, where the Geoenvironmental Susceptibility was obtained. The results show that in the Ribeirão Lajeado watershed there are four types of units: low, medium, high and very high Susceptibility. The low susceptibility unit is characterized by being a flat top area with vegetation cover and no proximity to roads. The medium Susceptibility unit are places that already have sparse human occupations, but the natural conditions are less susceptible to erosion processes. The high susceptibility unit covers areas where access is facilitated by the wide occurrence of roads and abundant drainage network, susceptible to human intervention due to access to them. The unit of very high Susceptibility is characterized by the presence of access given by several roads, portions of agricultural use with slopes greater than 15%, presence of fire scars and urban areas. The general way as areas with greater Geoenvironmental susceptibility coincides with the overlap of the Serra do Lajeado environmental protection area and the smaller ones with the Lajeado state park.